The Letter Laudato si' of Pope Francis: from object of attack to ignored document - Chaves O., Jorge Arturo (2022)
Several points of the Laudato si' Letter clash head-on with the hegemonic economic doctrine and with aligned politicians who defend it. It is the most notable pontifical document that deals systematically with ecological issues, presenting an articulating analysis of the main dimensions of the problems that afflict “our common home”. One of its most outstanding characteristics is the overcoming of reductionist and unidisciplinary excluding approaches, with the proposal to build an integrative approach. From this perspective, it sees all the problems diagnosed, which affect life on planet Earth, as consequences of the dominant technocratic paradigm ‒dominant to the point that it constitutes a paradigm of understanding that conditions people’s lives and the functioning of society, where finance continues to drown the real economy. For Francisco, it is a fabricated conception of the market, because it tends to think that problems are solved only with the growth of the profits of companies and individuals. It is tremendously risky that the techno-scientific power of this paradigm resides in a small part of humanity. An alternative paradigm would imply, among other things: redefining the concept and practice of progress, proposing solutions from the perspective of all those affected, establishing insurmountable limits to the protection of ecosystems, creating jobs by promoting an economy that favors productive diversity and entrepreneurial creativity. It requires changing the mentality, the global development model and questioning the logic underlying the current culture, moving towards a courageous cultural revolution.